Influence of different plantain cropping systems on physical properties of soil and plantain bunch yield - Tueche, J.R.; Hauser, S.; Banful, B.; Cadisch, Georg (Informa UK Limited, 2011)
Information on the effects of soil physical properties on plantain yield is rare. A factorial trial was conducted in three southern Cameroonian villages comparing four cropping systems comprising: two planted legumes, (1) Flemingia macrophylla and (2) Pueraria phaseoloides; a crop, (3) hot pepper; and (4) natural regrowth, all planted to plantain established in old forest versus young bush fallow. Initially, bush fallow had significantly higher sand content, mean weight diameter (MWD) and proportion of macroaggregates, but lower clay content and lower proportions of mesoaggregates and microaggregates than forest soil. Between 2002 and 2006, clay and silt content, MWD, geometric mean diameter and the proportion of macroaggregates increased, whereas sand content, bulk density, and the proportions of mesoaggregates and microaggregates decreased in all villages, fallows and cropping systems. Changes in aggregate stability parameters were greater in forest than in bush fallow at Ngoumou and Mfou, and greater in the F. macrophylla and natural regrowth systems than in the pepper and Pueraria systems. In Ngoumou and Nkometou, available water capacity increased. Plantain fresh-bunch yield was unaffected by village, fallow and cropping systems, and was not correlated with soil physical properties or their changes.